Volume 6: Energy 2017
DOI: 10.1115/imece2017-70117
|View full text |Cite
|
Sign up to set email alerts
|

Design and Potential Application of Small Scale Wave Energy Converter

Abstract: Although theoretical available wave energy is higher than most of ocean energy sources, the commercial utilization of wave energy is much slower than other ocean energy sources. The difficulty of integration with the electrical grid system and the challenges of the installation, operation and maintenance of large energy generation and transmission systems are the major reasons. Even though there are successfully tested models of wave energy converters, the fact that wave energy is directly affected by wave hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Figure 21 indicates that the absence of wind EEs was rare for low thresholds throughout the year while the absence of wind EEs for high thresholds increased from May to September. Weak wind EEs correlate with seasonal low summer wave power density levels in the GoM found in previous research [28,29,32]. Figure 22 shows the number of months without wave EEs above certain thresholds over 36 years.…”
Section: Low Levels Wave Energy In the Gomsupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 21 indicates that the absence of wind EEs was rare for low thresholds throughout the year while the absence of wind EEs for high thresholds increased from May to September. Weak wind EEs correlate with seasonal low summer wave power density levels in the GoM found in previous research [28,29,32]. Figure 22 shows the number of months without wave EEs above certain thresholds over 36 years.…”
Section: Low Levels Wave Energy In the Gomsupporting
confidence: 58%
“…Previous research has indicated that there is a significant theoretical wave energy resource in the GoM to provide great benefits to the local economy if optimally extracted [28][29][30][31]. In addition, the combination of wave energy with other ocean renewable energy resources at the GoM is very interesting with very large potential and possibility for combining wind energy with wave energy [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of the Equations (1) to (4) above is that maximum theoretical power to be extracted from a sea wave has a relationship between the wave energy fluxes per unit length of a wave crest (the resource potential) as described in the following equations [115][116][117]. P is the average power produced at a particular period.…”
Section: (M + A)mentioning
confidence: 99%
“…Despite these setbacks, Masuda [59,60] has demonstrated that ocean waves could supply a reliable source of energy. Following more theoretical analyses into wave energy dynamics [29][30][31], the 1980s and the early 2000s saw many bold attempts regarding the design and construction of WEC prototypes around the world. The capacities of those major WECs and their prototypes ranged from tens of kW to several hundreds of kW, as shown in Table 2.…”
Section: Oscillating Water Column Devicesmentioning
confidence: 99%
“…The performance of WECs can be greatly influenced by the wave condition at the test sites. For example, the performance of oscillating water columns and oscillating body systems, whose optimum capture occurs when the WEC is at resonance with the incoming waves [31][32][33][34][35], will be much lower if the WECs are tested in a site where most of the wave properties are outside the WEC's resonance bandwidth.…”
mentioning
confidence: 99%